ANALISIS PENDAPATAN DAN PROFITABILITAS INDUSTRI MEUBEL ROTAN TORA-TORA DI KOTA PALU SULAWESI TENGAH - AliminLaihi,Rustam AbdRauf,Lien damayanti, Alfit (AGROTEKBIS, 2015)
Central Sulawesi province is one of the rattan producing areas, therefore the rattan furniture industry is highly prospective for development in Palu City. One of the industries that manage rattan into various handicrafts are wicker furniture industry is Tora-Tora. It has production industry, that is quite high. However, it is still not able to properly inform its financial statements. The research objective titled analysis of revenue and profitability of the rattan furniture industry Tora-Tora in the Palu city is to determine the amount of income and profitability of rattan products industry "Tora-Tora" in Palu during the past year in 2014. The location determination is done intentionally (purposive) with the consideration that the rattan furniture industry is one of the largest industries producing rattan to three. Respondents in this study is the leadership and employees of Rattan Furniture Tora-Tora. Respondent committed intentionally (purposive) with the consideration that the leadership of the company and the employee can provide information about their business and know the financial condition of its business. Collecting data in this study consist of primary data and data sekunder. Analysis data used is the analysis of revenue and profitability by using Return on assets and return of analysis used business assets Gross profit margin, net profit margin, return on Investment). The results showed that the profitability of businesses rattan products tora-tora Return on Assets showed a 0,14indicates that the ability of the company utilizes its assets to generate profits by 0,14. Profitability in the asset recovery business value Gross profit margin of 0,10 indicates that the company's ability to produce a gross profit of the total value of sales is the profit earned. Net Value Profit Margin of 0,05indicates that the company's ability to produce the net profit of the level of sales or sales volume. Return on Investment value of 0,10indicates that the company's ability to generate funds invested overall profit of 0,10.